Comparison of the Effects of Dexamethasone and Ondansetron on the Reduction of Postoperative Nausea and Vomiting following Cesarean Section under Spinal Anesthesia - Nejadi, Jahanbakhsh R.; Shamseh, Mahnaz; Ronasi, Nooshin; Birjandi, Mehdi; Karimi, Arash (Current Reviews in Clinical and Experimental Pharmacology, 2021)
Background: Postoperative Nausea and Vomiting (PONV) is a common complication associated with the use of anesthesia. Several antiemetics are used to reduce the incidence and severity of PONV. The aim of this study was to investigate the role of dexamethasone and ondansetron to treat PONV in patients undergoing cesarean section (c-section) under spinal anesthesia. Methods: This double-blind clinical trial study was performed on patients who were referred to Haji Karim Asali Hospital of Khorramabad for elective cesarean section in 2016-17. Upon meeting the inclusion criteria, patients were allotted into two groups (n=60). Group A received 8mg of dexamethasone and group B received 4mg of ondansetron after spinal anesthesia. The Visual Analog Scale (VAS) questionnaire and Depression-Anxiety-Stress Scale (DASS) questionnaire were used for the analysis. Patients with mild to moderate stress, anxiety, and depression were included in the study. Data were analyzed using SPSS 16 software. Results: There was no difference in the demographic data of the two groups. The mean severity of nausea in group A was significantly higher than in group B. The odd ration of PONV was 20.67, which was found to be statistically significant, p = 0.018. Concerning the type of delivery with the frequency of nausea, the results showed that the frequency of nausea in group A was 3.24 times higher than group B, however, this difference was not statistically significant, p = 0.106. Conclusion: Based on the results of this study, ondansetron had a significant effect on the alleviation of postoperative nausea and vomiting, as compared to dexamethasone in C-section surgical candidates.
Keywords: nausea